The Effect of Service Quality on Passenger Satisfaction at Tingkir Bus Terminal, Salatiga City - Aderia Rimitha Djami; Roesjanto Roesjanto; Wasi Sumarsono (Shipping and Transport Management Journal, 2025)
This study aims to analyze the effect of service quality on passenger satisfaction at Tingkir Bus Terminal, Salatiga City. Service quality is an essential factor in achieving customer satisfaction, especially in public transportation services that cater to the needs of the community. The study underscores the importance of efficient and reliable services in improving the overall passenger experience. This research uses a quantitative approach, employing a survey method with 100 respondents who are passengers at the terminal. Data were collected through a Likert-scale questionnaire, designed to measure various aspects of service quality such as timeliness, comfort, and customer support. The data were analyzed using SPSS version 26, with procedures including validity tests, reliability tests, simple linear regression, and hypothesis testing (t-test). The results show that service quality has a positive and significant effect on passenger satisfaction, suggesting that higher service quality leads to increased satisfaction. This finding emphasizes the critical role of service quality in enhancing the operational success of public transportation services. The study’s findings are expected to serve as valuable evaluation material for improving service quality and provide practical insights for terminal management to enhance passenger satisfaction in the future.